Hospital-wide antigen screening for coronavirus disease in a tertiary reference center in Sapporo, Japan: A single-center observational study. Issue 51 (23rd December 2021) - Shimamura, Yoshinosuke; Komazawa, Hiroki; Oikawa, Junko; Furuta, Yasushi
Abstract : Abstract: Hospital-wide screenings for coronavirus disease (COVID-19) are important to identify healthcare workers at risk of exposure. However, the currently available diagnostic tests are expensive or only identify past infection. Therefore, this single-center observational study aimed to assess the positivity rate of hospital-wide antigen screening tests for COVID-19 and evaluate clinical factors associated with antigen positivity during a COVID-19 institutional outbreak in Sapporo, Japan. We analyzed the data of 1615 employees who underwent salivary or nasal swab antigen tests on November 18, 2020, to detect severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Laboratory confirmation using reverse transcriptase polymerase chain reaction was performed for those with positive viral serology. The demographic characteristics, job titles, and risk of contact with COVID-19 patients were compared between employees with and without COVID-19. A total of 19 employees (1.2%) tested positive for the SARS-CoV-2 antigen. The positivity rate was high among rehabilitation therapists (2.1%) and employees in the low-risk contact group (6.1%). Although there was no association between the job titles and the seropositivity rate, those in the low-risk contact group had an increased risk of testing positive for the viral antigen (odds ratio, 8.67; 95% confidence interval, 3.30–22.8). The antigen positivity rate was low during the hospital outbreak, suggesting that risk assessment of exposure to COVID-19 patients may provide more useful information than using job titles to identify infected health care providers.